2009
DOI: 10.2174/1875399x00902010058
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Physical Activity Monitors in Assessing Energy Expenditure in Normal, Overweight, and Obese Adults

Abstract: A comparison of the validity of downloadable motion sensors, which use either a glass-enclosed magnetic reed proximity switch technology, a piezo-electric sensor accelerometer with a horizontal beam technology, or an internal pendulum based mechanism to determine energy expenditure (EE), across different body sizes does not exist. Therefore, the purpose of this study was to determine the validity of three different downloadable motion sensors to estimate EE during walking activity in normal weight, overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 10 publications
(11 reference statements)
1
28
0
Order By: Relevance
“…Pedometers are economically feasible for use in large studies and the use and validity of them in physical activity research has been systematically reviewed (Corder et al 2007;De Vries et al 2009;Tudor-Locke et al 2002) by comparing the results of different brands (Ayabe et al 2008;Basset et al 1996Basset et al , 2000Beets et al 2005;Crouter et al 2003Crouter et al , 2005Doyle et al 2007;Le Masurier et al 2004;Melanson et al 2004;Nakae et al 2008;Schneider et al 2004;Swartz et al 2009) and by examining the accuracy of step taken (Ayabe et al 2008;Basset et al 1996;Crouter et al 2003Crouter et al , 2005Doyle et al 2007;Holbrook et al 2009;Le Masurier and Tudor-Locke 2003;Le Masurier et al 2004;Nakae et al 2008;Rowlands et al 2007), distance traveled (Basset et al 1996;Crouter et al 2003;Karabulut and Crouter 2005;Schneider et al 2003), and energy expenditure (Bassett et al 2008;Crouter et al 2003;Nelson et al 1998;Swartz et al 2009). There are plenty of studies which examined the accuracy, reliability, and validity of using pedometers in adults and children population (Ayabe et al 2008;Basset et al 1996Basset et al , 2000Beets et al 2005;<...>…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedometers are economically feasible for use in large studies and the use and validity of them in physical activity research has been systematically reviewed (Corder et al 2007;De Vries et al 2009;Tudor-Locke et al 2002) by comparing the results of different brands (Ayabe et al 2008;Basset et al 1996Basset et al , 2000Beets et al 2005;Crouter et al 2003Crouter et al , 2005Doyle et al 2007;Le Masurier et al 2004;Melanson et al 2004;Nakae et al 2008;Schneider et al 2004;Swartz et al 2009) and by examining the accuracy of step taken (Ayabe et al 2008;Basset et al 1996;Crouter et al 2003Crouter et al , 2005Doyle et al 2007;Holbrook et al 2009;Le Masurier and Tudor-Locke 2003;Le Masurier et al 2004;Nakae et al 2008;Rowlands et al 2007), distance traveled (Basset et al 1996;Crouter et al 2003;Karabulut and Crouter 2005;Schneider et al 2003), and energy expenditure (Bassett et al 2008;Crouter et al 2003;Nelson et al 1998;Swartz et al 2009). There are plenty of studies which examined the accuracy, reliability, and validity of using pedometers in adults and children population (Ayabe et al 2008;Basset et al 1996Basset et al , 2000Beets et al 2005;<...>…”
Section: Introductionmentioning
confidence: 99%
“…There are plenty of studies which examined the accuracy, reliability, and validity of using pedometers in adults and children population (Ayabe et al 2008;Basset et al 1996Basset et al , 2000Beets et al 2005;Crouter et al 2003;De Vries et al 2009;Doyle et al 2007;Nakae et al 2008;Schneider et al 2003Schneider et al , 2004 and in obese and non-obese population Hasson et al 2009;Holbrook et al 2009;Le Masurier et al 2004;Melanson et al 2004;Swartz et al 2009, found that 8-10 electronic pedometers were considered accurate in measuring steps. The accuracy of pedometers depends on the level of the speed.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some conflicting reports of the effect of waist adiposity on the tilt angle of the monitor, and consequently on the output of some activity devices (Swartz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Crouter et al [18] reported that the mean numbers of steps generated by six of 10 pedometers fluctuated within ±1% of the actual numbers of steps at 80, 94 and 107 m/min, and five of these were manufactured in Japan. Schneider et al [25] determined the accuracy and reliability of 10 pedometers for measuring steps over a 400-m distance. They found that the Japanese pedometers were the most accurate, being within ±3% of the actual steps.…”
Section: Discussionmentioning
confidence: 99%
“…The OMRON HJ-720 and HJ-113 pedometers speed-dependently underestimate energy expenditure measured as kilocalories by up to 28% [16]. Conversely, the OMRON HJ-700IT pedometer tends to overestimate energy expenditure at various speeds [25]. Crouter et al [18] found that eight pedometers generated higher-than-average amounts of expended calories compared with actual values.…”
Section: Introductionmentioning
confidence: 98%